2011
DOI: 10.1103/physreve.84.031403
|View full text |Cite
|
Sign up to set email alerts
|

Impact of spherical projectiles into a viscoplastic fluid

Abstract: We study the behavior of a yield-stress fluid following the impact of a vertically falling sphere. Since the impact produces shear stresses larger than the yield stress, the material in the vicinity of the impact becomes fluidized. The sphere entrains air when it enters the fluid, and the resulting cavity pinches off below the surface. The upper part of this cavity then rebounds upward. For sufficiently fast impacts, a vertical jet is produced by the cavity collapse. While many aspects of this process are simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…Particularly, a liquid droplet impact either onto a liquid pool or a hard floor has been studied well so far [2]. A solid sphere impact to a non-Newtonian target fluid has been also investigated experimentally [5,6]. Furthermore, some recent studies have concerned granular target impacts as well as fluid target impacts.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, a liquid droplet impact either onto a liquid pool or a hard floor has been studied well so far [2]. A solid sphere impact to a non-Newtonian target fluid has been also investigated experimentally [5,6]. Furthermore, some recent studies have concerned granular target impacts as well as fluid target impacts.…”
Section: Introductionmentioning
confidence: 99%
“…We suppose that the current experiment is still in the low-R e regime. In the viscoplastic impact experiment, 17 crater diameter and cavity pinch-off depth showed almost constant values in the low-R e regime, i.e., R e < 10. This implies that the low-R e regime lasts until R e ' 10.…”
Section: Discussionmentioning
confidence: 95%
“…Cheny and Walters have found that jet formation is very sensitive to the viscoelasticity of the target fluid. 15 Crater morphology, penetration, and rebound properties have been discussed for viscoelastic 16 and viscoplastic 17 fluids.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(3.7)) was also used as a target of the solid sphere's impact experiment [122]. (3.7)) was also used as a target of the solid sphere's impact experiment [122].…”
Section: Viscoplastic Fluid Dragmentioning
confidence: 99%